Off-label use of antimicrobials among hospitalized children: a retrospective study of 3,406 patients - Tang, Lin; Zhao, Kai; Hou, Ning (Frontiers in Microbiology, 2023)
Introduction Off-label drug use is a global problem for which many countries and regions have issued legal provisions or reached an expert consensus. Off-label use is sometimes a necessity, especially since antibacterial drugs have become one of the most widely used drugs in pediatric settings and the issue of causing antimicrobial resistance has increasingly become unavoidable. It also poses additional risks, such as adverse drug reactions. Methods Our study analyzed the antimicrobial prescriptions of pediatric inpatients in a large Chinese hospital in the first half of 2021. This retrospective investigation included 6,829 prescriptions, including 2,294 off-label prescriptions. We performed descriptive analyses of prescription antimicrobial agents among pediatric populations and reported the percentages and frequencies. Results It was found that off-label use of antibiotics was present in many children (n = 1,665, 48.9%) and was most common in newborns (n = 328, 82.8%). Among the commonly used antibiotics in pediatric patients, cephalosporins (n = 2,778, 40.7%) accounted for a relatively low proportion of offlabel use (n = 360, 15.7%), while macrolides (n = 628, 27.4%) and penicillins (n = 610, 26.6%) accounted for a higher proportion. The off-label type mainly referred to the appropriate population (46.5%) and dosage (dose, 10.0%; frequency of administration, 48.3%). Discussion Off-label use was due to imperfect labels, improper medications, or medication errors. Only a few consensuses could apply to pediatric patients. More clinical trials are required to update the consensus, and drug labels must be continuously improved. The prescription behavior of doctors is also needed to be regulated. Rational use of drugs, especially antimicrobials, is the responsibility of all people, including the states, medical institutions, and individuals.